Hybrid endoscopic-microscopic surgery for dumbbell-shaped trigeminal schwannoma: case report and literature review - Li, Xinning; Han, Song; Sun, Xiaoyu; Bai, Yang; Zhang, Qiyan; Feng, Sizhe; Liang, Guobiao (Frontiers in Oncology, 2023)
Background: The surgery of dumbbell-shaped trigeminal neurinomas (TN) remains one of the most formidable challenges for neurosurgeons because of its location at great depth in the cranium and proximity to vital neurovascular structures. Objective: To describe the feasibility of a novel technique, synchronous endoscopy and microsurgery via combined far-lateral supracerebellar-infratentorial and subtemporal approach, for resection of this rare entity. Methods: A 53-year-old women presented with progressive left facial numbness for 2 months. Imaging examinations revealed a left-sided dumbbell-shaped TN afflicting the middle and posterior cranial fossa, and a single-stage combined multiportal endoscopic microscopic approach was attempted for tumor resection. Initially, a purely endoscopic far-lateral supracerebellar-infratentorial approach was used to remove the posterior fossa component with the aid of tentorium incision. Subsequently, a microsurgical subtemporal interdural approach was performed for the exposure and separation of tumor within the Meckel cave. Finally, the tumor was pushed into the porus trigeminus under microscopy, thus enabling tumor extraction for the supracerebellar space under endoscopy without anterior petrosectomy. Results: The patient evolved favorably without additional neurological deficit after surgery, and postoperative imaging showed a complete resection of the tumor. Conclusion: We describe the first account of multi-corridor hybrid surgery for removal of TN in a dumbbell configuration, which enables one-stage total tumor removal with minimal added morbidity. This hybrid technique may be an effective piece of the surgeon’s armamentarium to improve outcomes of patient with complex skull-base lesions. Further studies with larger case numbers are warranted to confirm the prognostic significance of this technique.